CD10 inhibits cell motility but expression is associated with advanced stage disease in colorectal cancer - Raposo, T.P.; Comes, Mireia Sueca; Idowu, Adeyemi; Agit, Bora; Hassall, James; Fadhil, Wakkas; Nica, Robert; Ecker, Rupert; Yao, Takashi; Ilyas, Mohammad (Elsevier, 2018)
Introduction CD10 is a cell membrane-bound endopeptidase which is expressed in normal small bowel but not in normal colon. It is aberrantly expressed in a small proportion of colorectal cancers (CRC) and this has been associated with liver metastasis and poor prognosis. We sought to investigate the mechanism of CD10 activity and its association with clinicopathological features.